Simons Observatory: Characterization of the Large Aperture Telescope Receiver - Tanay Bhandarkar; Saianeesh K. Haridas; Jeff Iuliano; Anna Kofman; Alex Manduca; Karen Perez Sarmiento; John Orlowski-Scherer; Thomas P. Satterthwaite; Yuhan Wang; Zeeshan Ahmed; Jason E. Austermann; Kyuyoung Bae; et al. (The Astrophysical Journal Supplement Series)
The Simons Observatory (SO) is a ground-based cosmic microwave background (CMB) survey experiment that currently consists of three 0.42 m small-aperture telescopes and one 6 m large-aperture telescope (LAT), located at an elevation of 5200 m in the Atacama Desert in Chile. At the LAT’s focal plane, SO will install >62,000 transition-edge sensor detectors across 13 optics tubes (OTs) within the Large Aperture Telescope Receiver (LATR), the largest cryogenic camera ever built to observe the CMB. Here we report on the validation of the LATR in the laboratory and the subsequent dark testing and validation within the LAT. We show that the LATR meets cryogenic, optical, and detector specifications required for high-sensitivity measurements of the CMB. At the time of writing, the LATR is installed in the LAT with six OTs (corresponding to >31,000 detectors), and the LAT mirrors and remaining seven OTs are undergoing development.